2021
DOI: 10.3390/fi13020044
|View full text |Cite
|
Sign up to set email alerts
|

Digital Regulation of Intellectual Capital for Open Innovation: Industries’ Expert Assessments of Tacit Knowledge for Controlling and Networking Outcome

Abstract: Digital regulation implies the quantified measuring and the network infrastructure allowing managers to control the processes of value creation. Digital regulation needs to take into account tacit elements of the value creation process, including unconscious competency, creativity, and intuitive anticipation, to assure the resulting network’s innovation growth. Digital society in developing countries is built on the ground of fact change of the economy and social relations, of transition towards an emerging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 66 publications
0
9
0
1
Order By: Relevance
“…Relación directa entre el apoyo de la gestión y el capital intelectual Cuando las organizaciones logran transformar el conocimiento recién adquirido en activos capaces de generar riqueza y ventajas competitivas, junto con la habilidad para fusionar experiencias y saberes, se puede afirmar que poseen Capital Intelectual (Pokrovskaia et al, 2021;Quintero-Quintero et al, 2021). El CI se apoya en el talento del personal, el valor de los conocimientos y el seguimiento a los procesos internos.…”
Section: Fundamentación Teórica Y Desarrollo De Hipótesisunclassified
“…Relación directa entre el apoyo de la gestión y el capital intelectual Cuando las organizaciones logran transformar el conocimiento recién adquirido en activos capaces de generar riqueza y ventajas competitivas, junto con la habilidad para fusionar experiencias y saberes, se puede afirmar que poseen Capital Intelectual (Pokrovskaia et al, 2021;Quintero-Quintero et al, 2021). El CI se apoya en el talento del personal, el valor de los conocimientos y el seguimiento a los procesos internos.…”
Section: Fundamentación Teórica Y Desarrollo De Hipótesisunclassified
“…Research has found that an organization's intellectual capital has a positive effect on employee's innovative behavior, and it comprises human capital, structural capital, and customer capital (Sun, 2021;Ullah et al, 2021). Previous studies have explored the effects of these elements on business performance, but their effects on employees' innovative behavior require further investigation (Pokrovskaia et al, 2021). Therefore, investigating the relationship between intellectual capital and the multidimensional measure of an individual's innovative work behavior in the workplace is crucial (Narzary & Palo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the pandemic causes the inability to promote employees, and a decrease in creativity, in which HC still requires improvement and leadership through individuals in the company (Pokrovskaia et al, 2021). To engage or join in innovative and complex projects, small businesses must provide resources as they lack these necessary resources, such as HC and financial resources (Chierici Tortora, Del Giudice, & Quacquarelli, 2020).…”
Section: Introductionmentioning
confidence: 99%